Hypothermia-Mediated Apoptosis and Inflammation Contribute to Antioxidant and Immune Adaption in Freshwater Drum, Aplodinotus grunniens - Jianxiang Chen; Hongxia Li; Pao Xu; Yongkai Tang; Shenyan Su; Guangxiang Liu; Ningyuan Wu; Miaomiao Xue; Fan Yu; Wenrong Feng; Changyou Song; Haibo Wen (Antioxidants, 2022)
Hypothermia-exposure-induced oxidative stress dysregulates cell fate and perturbs cellular homeostasis and function, thereby disturbing fish health. To evaluate the impact of hypothermia on the freshwater drum (Aplodinotus grunniens), an 8-day experiment was conducted at 25 °C (control group, Con), 18 °C (LT18), and 10 °C (LT10) for 0 h, 8 h, 1 d, 2 d, and 8 d. Antioxidant and non-specific immune parameters reveal hypothermia induced oxidative stress and immunosuppression. Liver ultrastructure alterations indicate hypothermia induced mitochondrial enlargement, nucleoli aggregation, and lipid droplet accumulation under hypothermia exposure. With the analysis of the transcriptome, differentially expressed genes (DEGs) induced by hypothermia were mainly involved in metabolism, immunity and inflammation, programmed cell death, and disease. Furthermore, the inflammatory response and apoptosis were evoked by hypothermia exposure in different immune organs. Interactively, apoptosis and inflammation in immune organs were correlated with antioxidation and immunity suppression induced by hypothermia exposure. In conclusion, these results suggest hypothermia-induced inflammation and apoptosis, which might be the adaptive mechanism of antioxidation and immunity in the freshwater drum. These findings contribute to helping us better understand how freshwater drum adjust to hypothermia stress.